Compact superconducting lowpass filter with wide stopband. Issue 14 (1st July 2017) - Jiang, Ying; Wei, Bin; Heng, Yong; Guo, Xubo; Cao, Bisong; Jiang, Linan
Abstract : A compact superconducting lowpass filter (LPF) composed of a pair of symmetrical parallel coupled lines, a cross‐shaped patch and a modified E‐type feeding structure is proposed. The filter is successfully designed and fabricated on MgO substrate with a compact size of 10.0 × 15.0 mm. Measured results match well with simulation results. The LPF has a 3 dB cut‐off frequency of 2.18 GHz, relative stopband bandwidth of 160%, and 0.06 dB insertion loss in the passband. For attenuation level of −18.5 dB, stopband bandwidth is from 3.16 to 19.25 GHz.